Perlindungan Hukum Penjual terhadap Pembatalan Sepihak oleh Pembeli pada Sistem Cash on Delivery - Putri Ramadhani, Yuli Eka; Fitrian, Achmad; Wibisono, Arief (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The rapid evolution of technology has significantly impacted commerce, transforming traditional buyer-seller interactions. New payment systems, notably Cash on Delivery (COD), have emerged, where buyers either prepay or settle upon delivery. However, COD has faced challenges, with some buyers exploiting loopholes by rejecting deliveries for various reasons. This study employs a juridical normative approach to investigate legal safeguards for sellers against unilateral cancellations within the COD system. Analyzing the ordering process and relevant regulations, the research asserts that issues in online purchases, including COD, arise only when either party breaches the agreement. A product return feature addresses discrepancies in received goods. The legal foundation for sellers' protection lies in Article 1243 of the Civil Code, reinforced by Articles 1320, 1338, 1313, and 1458. This framework provides certainty for businesses engaged in online transactions with COD, securing rights and obligations for both parties. The research emphasizes the importance of these legal measures to mitigate financial losses resulting from unjustified cancellations, ensuring a fair and regulated environment for online commerce.